Coloniality of knowledge, hybridisation, and indigenous survival: exploring transnational higher education development in Africa from the 1920s to the 1960s. Issue 4 (4th July 2019) - Poloma, Asabe W.; Szelényi, Katalin
Abstract: This historical multi-case study uses the concepts of coloniality of knowledge, critical hybridity, and indigeneity in examining higher education development in Africa through the efforts of Nnamdi Azikiwe of Nigeria and Kwame Nkrumah of Ghana, two educational reformers and former international students in the USA. We develop a framework for examining how transnational interactions between the Global North and the Global South shape higher education development. Implications are presented for the importance of flexible theoretical understandings of transnational higher education interactions as well as higher education practices in international student and scholar exchange and other transnational higher education engagement.